Effect of Magnetic Flux on Rotor-Stator Arrangement of Neodymium Permanent Magnet - A. R., Razali; M., Ishak; Nazrul Idzham, Kasim; Mohd Azam, Musa (Asian Research Publishing Network (ARPN), 2015)
The use of crude oil to produce energy become limited and gives threat to the earth. There are various alternative sources that have been developed today such as solar, wind, hydro, etc., but are not sustainable or constant with time due to its nature. Recent development in ‘free energy’ shows some technology that allegedly approaching commercial and magnet motor is one of the most promising technologies. Magnet motor is a free energy device that can generate energy with the repellent force of permanent magnet in cylindrical arrangement. The arrangement of permanent magnet in rotational array configuration produces a cyclic motion indefinitely; which is so called perpetual motion device. The torque produced by perpetual motion device may be used to drive electric generator to produce free electricity. In this paper, neodymium permanent magnet was arranged in rotor-stator configuration by using block shape (12.7 mm x 12.7 mm x 25.4 mm thickness) N42 grade magnet. A preliminary design was conducted and the effect of magnetic flux was investigated on the rotational movement of the rotor. Based on the experimental result, it had confirmed that cogging effect could be eliminated. This was achieved by cancellation of magnetic flux in different arrangement of permanent magnet in the stator.